Corporate long-range planning in South Africa: its extent and nature - Kabat, Miroslav (School of Architecture, Planning and Geomatics, 2020)
This thesis was written in response to the increasingly evident need for the most complete information possible on planning activity and practices among South African firms. It was also dictated by an urgent necessity to clarify the methodologies, techniques and frameworks used at present in business planning. Alas, only too often scholars and practitioners alike assume that a comprehensive and general theory on planning exists, complete with methodologies, models, frameworks and so forth. But anyone examining the vast amount of literature on planning and related subjects published during the past twenty years would find this to be a fallacy, and may experience the same desire for the clarification of the present status of the planning art as we did. This desire became one of the principal stimuli for our investigation. Some studies may be built on already well-established foundations, but this is unfortunately not the case in our enquiry as there is as yet no appreciable base consisting of a distinct body of knowledge and relevant theories. In attempting to delineate this knowledge, a necessary point of departure is an appraisal of the current state of human knowledge. We shall, therefore, start with a broad review of this knowledge and narrow it down to areas which are particularly relevant to business planning. This attempt will, hopefully, point to a body of distinct knowledge indispensable to modern planners and show that, - whilst a large body of this knowledge lies within a discipline called 'management science', other relevant knowledge is found in economics, organisation theory and theory of knowledge. This analysis will, at the same time, highlight the present status of the relevant theory of planning, and indicate gaps between the state of the art and the needs of the business. We shall suggest that a general planning theory must come from an interdisciplinary approach. The aim of these efforts is to develop a broad framework and guide for our analysis of planning activity, concepts and methodologies at present used by South African firms. On the basis of these findings we shall than make judgements on the manner in which South African planners address each of the descriptive and normative planning topics, and suggest possible directions for further research. Finally, we shall attempt to formulate a conceptual long-range planning model as we see it, and discuss the usefulness of formal, mathematical planning models as revealed by our study and survey.